The evaluation of social capital benefits: enterprise level - Mačerinskienė, Irena; Aleknavičiūtė, Giedrė (Business, Management and Economics Engineering, 2011)
This paper aims to present how social capital can benefit business processes of an enterprise, which uses its social networks for business purposes, and which of those benefits are the most important in this context. The first part of this article represents the theory of social capital. The main conceptual approaches to social capital were investigated. According to this, the conception of social capital and its dimensions were introduced. The second part of this paper seeks to evaluate the benefits of social capital to enterprise’s business activities by mentioning not only benefits, which create social capital but also risks, which can occur if social capital is used improperly. The last part of this essay introduced the model of social capital’s benefits to enterprise’s business processes and evaluated, which of them are the most relevant.